The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1128/mcb.20.4.1329-1343.2000
|View full text |Cite
|
Sign up to set email alerts
|

TATA-Binding Protein–TATA Interaction Is a Key Determinant of Differential Transcription of Silkworm Constitutive and Silk Gland-Specific tRNAAla Genes

Abstract: We have investigated the contribution of specific TATA-binding protein (TBP)-TATA interactions to the promoter activity of a constitutively expressed silkworm tRNA C Ala gene and have also asked whether the lack of similar interactions accounts for the low promoter activity of a silk gland-specific tRNA SG Ala gene. We compared TBP binding, TFIIIB-promoter complex stability (measured by heparin resistance), and in vitro transcriptional activity in a series of mutant tRNA C Ala promoters and found that specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…the 2 35 TTTTTC element in C. elegans), even though TATA-like sequences might be present and play important roles in special cases. 5,6 Also, completely new blocks of sequence conservation, located near position 2 20, appear in insect and mammals, as exemplified by the nearly identical A-rich motif found at position 2 22 upstream of mouse and human tDNAs. Because of its striking evolutionary conservation, such a motif is likely to play an important role in mammalian tRNA gene transcription.…”
Section: Sequence Features and Functional Implications Of Tdna Upstrementioning
confidence: 97%
See 1 more Smart Citation
“…the 2 35 TTTTTC element in C. elegans), even though TATA-like sequences might be present and play important roles in special cases. 5,6 Also, completely new blocks of sequence conservation, located near position 2 20, appear in insect and mammals, as exemplified by the nearly identical A-rich motif found at position 2 22 upstream of mouse and human tDNAs. Because of its striking evolutionary conservation, such a motif is likely to play an important role in mammalian tRNA gene transcription.…”
Section: Sequence Features and Functional Implications Of Tdna Upstrementioning
confidence: 97%
“…The differential in vitro activity of silkgland-specific and constitutive tRNA Ala genes in the silkworm, Bombyx mori, has long been known to be due to sequence elements upstream of the TSS, 4 and it has later been shown to rely on the interaction of the TBP component of TFIIIB with a TATA-like element upstream of the constitutive gene. 5,6 Recent analyses have further revealed the presence of TATA-like elements upstream of many Saccharomyces cerevisiae tDNAs, and of the majority of Arabidopsis thaliana and Schizosaccharomyces pombe tDNAs. 7,8 The presence of upstream TATA elements is thus not restricted to particular class III genes, such as SNR6 (coding for the U6 snRNA), that have long been known to support TFIIIC-independent TFIIIB recruitment in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…All three of these promoter elements are required for efficient transcription in vivo (Brow and Guthrie 1990;Eschenlauer et al 1993). Other examples include some A-and B-box-containing tRNA genes in plants (Yukawa et al 2000), yeast (Dieci et al 2000), and silkworm (Ouyang et al 2000), in which TATA boxes present in the 5Ј-flanking region greatly contribute to transcription efficiency. More recently, an analysis in Schizosaccharomyces pombe has revealed that in this organism nearly all tRNA and 5S genes contain a TATA box upstream of the transcription start site that is required for transcription (Hamada et al 2001).…”
Section: Structure Of Rna Polymerase III Promotersmentioning
confidence: 99%
“…There are hybrid promoters like the U6 snRNA gene in S. cerevisiae that contain both internal promoters and a TATA box 61,62 which contributes to better transcription. 63,64,65 Microsatellites -The different microsatellites arrangements between genera at the NTS region are the main contributors to the variation in the NTS length. It has been shown that there is a correlation between the length of the NTS region and the number of motif repetitions within each region of microsatellites in Rajiformes.…”
Section: Nts Regionmentioning
confidence: 99%